Design and Analysis of Large Stroke Piezoelectric Deflection Stage - Liu, Jingwei; Zhou, Anna; Hao, Chenglong; Cui, Liangyu (International Journal of Mechanical and Electrical Engineering, 2025)
In this paper, a deflecton stage, actuated by piezoelectric ceramics actuator and capable of rotating along both the X and Y axes via a Hooke-type flexible hinge mechanism, is meticulously designed. Utilizing three-dimensional modeling software, the flexible mechanism of the piezoelectric deflection stage is modeled in detail. Furthermore, ANSYS software is employed to conduct a finite element analysis (FEA) on the flexible hinge mechanism component of the piezoelectric deflection stage, focusing on characteristics such as stroke, load capacity, stiffness, and Modal and other properties. The analysis reveals that the deflection angles can achieve up to 3.32 mrad and 3.34 mrad respectively, while the first-order natural frequency stands at 385.93 Hz. These specifications adequately fulfill the stringent requirements of high-speed operation for a large-stroke deflection stage.